EMERGENCY UROLOGIC IN PREGNANCY - Putu Surya Utami (Universitas Udayana, 2013)
A variety of anatomical and physiological changes occurring during pregnancy, which can affect any organ system. Urological problems in pregnancy represent a diagnostic and therapeutic challenge. Urinary tract symptoms in pregnant women comprise urinary tract infection, acute pyelonephritis, acute urinary retention, hematuria, placenta percreta, nefrolithiasis, uropathy obstructive, and malignancy urologic. A multidisciplinary approach is necessary, from the anesthetic and obstetric team. In this review, I will discuss the common urological problems that occur during pregnancy and outline an approach to their management.